Assessment of lowering formaldehyde release of particleboards using urea as a scavenger by chamber, perforator and flask method. (February 2014) - Johnsson, B.; Roffael, E.; Behn, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Addition of urea to a melamine modified urea formaldehyde resin in the surface and core layer reduces significantly the formaldehyde release of the particleboards bonded therewith. Under the used boundary conditions (long press time) urea addition seems to have no noticeable negative impact on the physical–mechanical properties of the boards. The reduction of formaldehyde release due to urea addition as a scavenger can be followed by measuring the emission in the chamber according to EN 717-1, the perforator method according to EN 120 and the flask method as described in EN 717-3. The results reveal that under the used conditions a good correlation exists between the emission in the chamber and the corrected perforator values (R2 = 0·865), as well as between the chamber value and the formaldehyde emission measured by the 3h-flask method (R2 = 0·792) according to EN 717-3, a slightly better correlation was found between the measured flask values after 24 h and the emission in the chamber (R2 = 0·869). The correlations seem to hold in the emission range between 0·06 and 0·016 ppm.